2014
DOI: 10.1186/1756-3305-7-268
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of four widely used mosquito traps in Central Europe

Abstract: BackgroundTo monitor adult mosquitoes several trapping devices are available. These are differently constructed and use various mechanisms for mosquito attraction, thus resulting in different trapping sensitivities and efficacies for the various species. Mosquito monitoring and surveillance programs in Europe use various types of mosquito traps, but only a few comparisons have been conducted so far. This study compared the performance of four commercial trapping devices, which are commonly used in Europe.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 27 publications
6
70
3
Order By: Relevance
“…Various mosquito traps are commercially available for public consumers to reduce the mosquito nuisance and/or decrease the risk of mosquito-borne illness [8]. Could a network of traps be used as a protecting belt around inhabited areas to improve human comfort while preserving wetland biodiversity?…”
Section: Introductionmentioning
confidence: 99%
“…Various mosquito traps are commercially available for public consumers to reduce the mosquito nuisance and/or decrease the risk of mosquito-borne illness [8]. Could a network of traps be used as a protecting belt around inhabited areas to improve human comfort while preserving wetland biodiversity?…”
Section: Introductionmentioning
confidence: 99%
“…All trapping methods can be considered to have a different trapping efficacy for the various mosquito species (Silver, ; Lühken et al. , ). However, this has not yet evaluated for the different members of the An.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that abundance data from CDC traps underestimate many mosquito species (DiMenna et al 2006, Giberson et al 2007, Jansen et al 2009). For Culex species, it appears that some are more attracted to cues other than carbon dioxide from dry ice, such as different avian odors (Allan et al 2006, Shone et al 2006, Lühken et al 2014, and that traps using light collect fewer females of Cx. quinquefasciatus than traps without light , Mboera et al 2000a.…”
Section: Discussionmentioning
confidence: 99%